The Pengaruh Kompetensi Dan Pengetahuan Kewirausahaan Terhadap Keberhasilan Pelaku UMKM Binaan Dinas Koperasi Dan UKM Kabupaten Karawang Tahun 2023 - Abdilah Zulkarnaen; Dede Jajang Suyaman; Nunung Nurhasanah; Sony Hersona (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research was conducted to examine the influence of entrepreneurial competency and knowledge on the business success of MSMEs assisted by the Karawang Regency Cooperatives and SMEs Service. The issues discussed are 1) whether there is a relationship between competence and entrepreneurial knowledge. 2) Is there an influence between entrepreneurial competence and business success? 3) Is there an influence between entrepreneurial knowledge and business success? 4) Is there an influence between competency and entrepreneurial knowledge on business success? The data used in the research is primary data. The data analysis technique used was path analysis, with a sample of 399 MSMEs assisted by the Karawanf Regency Cooperatives and SMEs Service and the sampling method used in this research was simple random sampling. The results of this research show that there is a relationship between entrepreneurial competence and entrepreneurial knowledge with a low level of relationship, entrepreneurial competence influences the success of MSMEs assisted by the Karawang Regency Cooperatives and SMEs Service in 2023 by 2.81%, entrepreneurial knowledge influences the success of MSMEs assisted by the Cooperatives and SMEs Service Karawang Regency SMEs in 2023 amounted to 5.10% and entrepreneurial competence and knowledge influenced the success of SMEs assisted by the Karawang Regency Cooperatives and SMEs Service in 2023 amounted to 7.91%. Meanwhile, the remainder was influenced by other variables amounting to 92.09% (= 1 – 0.079) which were not studied (ԑ).